Building people up: Growth‐oriented leadership in the public sector. Issue 4 (1st November 2021) - Franken, Esme; Plimmer, Geoff; Malinen, Sanna K.; Bryson, Jane; Berman, Evan M.
Abstract: Public services face increasing and more varied demands, but public service managers often lack the resources to develop their staff to effectively deal with them. This paper identifies how public sector line managers can support their subordinates to not just cope with challenges, but also to grow and develop in the midst of them. It primarily draws on employee attributions of leader effectiveness, to identify growth‐oriented leadership behaviours. The framework is based on empirical data from two sequential phases of interviews, focus groups, and one‐on‐one discussions with employees and managers in the public sector. Five categories of growth‐oriented leadership behaviours were identified: managing the whole team, enabling self‐management, managing safe failures, supporting both career and personal growth, and recognising individual needs and contributions. Causation coding identified a set of processes through which these leadership behaviours supported staff to use networks, learn, and adapt. The developed framework can be used to enhance growth and development of public sector employees. Abstract : This article identifies growth oriented leadership behaviours, and accompanying processes, that foster the resilient employee behaviours of network leveraging, learning and adaptability. Both the leadership, and employee behaviours, identified in this study should help public servants and agencies adapt to change and aid the transfer of work experiences to enhanced capability.